2021
DOI: 10.1001/jamaneurol.2021.3180
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of 8 Plasma Amyloid-β 42/40 Assays in Alzheimer Disease

Abstract: Key Points Question How well does plasma amyloid-β 42/40 (Aβ42/40), measured using 8 different assays, detect brain Aβ pathology in the early stages of Alzheimer disease? Findings In this study, including 408 participants from 2 independent cohorts (BioFINDER and Alzheimer Disease Neuroimaging Initiative), plasma Aβ42/40 quantified using certain mass spectrometry–based methods showed better discriminative accuracy than immunoassays when identifying individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
382
2
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 255 publications
(410 citation statements)
references
References 20 publications
22
382
2
4
Order By: Relevance
“…These results add to the conflicting literature in which some studies suggest that plasma Aβ42 or Aβ42/40 ratio strongly correlated with brain Aβ (AUC = 88 to 97%) [21,25], while others suggest only a moderate association between plasma and PET assessments of Aβ [43,44]. Moreover, previous research revealed that IP-MS performed better than Simoa in terms of Aβ estimates [23], whereas we found similar discriminative accuracy using both techniques. Several biological and analytical factors may contribute to the divergence of our results.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…These results add to the conflicting literature in which some studies suggest that plasma Aβ42 or Aβ42/40 ratio strongly correlated with brain Aβ (AUC = 88 to 97%) [21,25], while others suggest only a moderate association between plasma and PET assessments of Aβ [43,44]. Moreover, previous research revealed that IP-MS performed better than Simoa in terms of Aβ estimates [23], whereas we found similar discriminative accuracy using both techniques. Several biological and analytical factors may contribute to the divergence of our results.…”
Section: Discussionsupporting
confidence: 71%
“…For example, biological factors such as peripheral Aβ expression accounts to >50% of the global plasma Aβ [45] and the modest fold-change between CU and CI in plasma (10–20%) compared to CSF Aβ (40– 60%) may lead to the high susceptibility of plasma Aβ measures to small variabilities in pre-analytical approaches and cohorts characteristics [20, 21, 44]. In addition, differences in the analytical performance of distinct techniques used to measure plasma Aβ can also play a role in the difference in performance found across studies [23]. We have shown lack of robust correlation between plasma Aβ values and the other AD-related plasma markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These plasma biomarkers are also those identified as the best predictors of AD (Palmqvist et al 2021 ), but here, the context of use is different, and their performance are event higher than for discriminating AD from non-AD. Other differences are noted such as the fact that Aβ 1–42 detection by IP-MS outperformed other Aβ 1–42 detections, but this was not the case when considering the Aβ 1–42 /Aβ 1–40 ratio, thus differently than when AD is the performance criterion (Janelidze et al 2021 ). As mentioned above, this could be partly explained by the fact that diseases other than AD showed pathological amyloid or tau profiles.…”
Section: Discussionmentioning
confidence: 99%